2019
DOI: 10.1016/j.radonc.2019.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Re-irradiation using carbon ions for recurrent head and neck malignancies after carbon-ion radiotherapy

Abstract: Background and purpose: Locoregional recurrence after carbon-ion radiotherapy (CIRT) for primary head and neck malignancies, such as malignant mucosal melanoma, adenoid cystic carcinoma, and sarcoma, occurs occasionally. However, the treatment options are limited. We report on the toxicity and efficacy of re-irradiation using carbon ions for recurrent head and neck malignancies after CIRT. Materials and methods: Data of 48 patients with recurrent head and neck malignancies treated with reirradiation with CIRT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 19 publications
0
35
1
3
Order By: Relevance
“…In this study, 49 patients (42.6%) presented with tumor infiltration of the orbital cavity, and 94 patients (81.7%) had tumors with infiltration of the base of the skull or the immediate surroundings. Furthermore, compared to prior studies on re-irradiation with heavy ions [21], the median PTV of 128.9 cc in this evaluation was extensive, reaching about 50-100% more. In addition, the tumor locations were possibly more challenging in the current analysis (81.7% of them infiltrated the base of the skull).…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…In this study, 49 patients (42.6%) presented with tumor infiltration of the orbital cavity, and 94 patients (81.7%) had tumors with infiltration of the base of the skull or the immediate surroundings. Furthermore, compared to prior studies on re-irradiation with heavy ions [21], the median PTV of 128.9 cc in this evaluation was extensive, reaching about 50-100% more. In addition, the tumor locations were possibly more challenging in the current analysis (81.7% of them infiltrated the base of the skull).…”
Section: Discussioncontrasting
confidence: 58%
“…Considering all patients for whom dose constraints were exceeded intentionally (n = 49, 42.6%), the dose prescription at CIR was restrictive in the current analysis. Hayashi et al [21] reported absolute dose constraints at CIR of 30 Gy (RBE) for the brainstem and spinal cord and 40 Gy (RBE) for the optic system. Hu et al [6] assumed a recovery from the previous photon radiotherapy set at 70%, independent of the RT interval.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the initial RT in our study was high-LET C-ion RT. Hayashi et al [15] reported that the 2-year LC following re-irradiation with C-ion RT in patients with head and neck malignancies whose tumours recurred after initial C-ion RT was 40.5%. This was inferior to the 2-year LC rates following initial C-ion RT reported by Koto et al [23] (83.9%).…”
Section: Discussionmentioning
confidence: 99%
“…Hayashi et al [15] evaluated 48 patients with recurrent head and neck malignancies treated with C-ion RT re-irradiation and reported 2-year LC and OS rates of 40.5% and 59.6%, respectively. This provided evidence that re-irradiation using carbon ions is a reasonable treatment with tolerable toxicity for patients with recurrent head and neck malignancies after C-ion RT.…”
Section: Introductionmentioning
confidence: 99%
“…Dmean to OaR was reduced by 86% using IMPT and by 100% when IMIT was used, with significant dosimetric sparing of the contralateral organs (carotid artery, arytenoid, parotid, and submandibular glands), spinal cord, and brainstem. 84 Particle re-irradiation could facilitate dose escalation in the tumor while sparing OaR, and with the expected reduction in long-term side effects of RT, it could also reduce the likelihood of normal tissue complication probability, 85 but any widespread recommendation on its use in clinical practice is biased by short follow-up [86][87][88][89][90][91][92] (Table 3). Available evidence includes only retrospective phase II studies without control arms and with a limited number of patients.…”
Section: Re-irradiation Using Heavy Ionsmentioning
confidence: 99%